Methodological aspects and creation of a basis of soil and cadastro data - Odintsov Stanislav Vladimirovich, Malochkin Vladimir Yuryevich, Loshakov Alexander Viktorovich,; Podkolzin Oleg Anatolyevich, Stukalo Vladimir Alexandrovich, (Opción, 2019)
The study aims to investigate methodological aspects and the creation of a basis of soil and cadastro data for the development of a land and information system based on modern information and geoinformation technologies. The results of the research developed a database of soil inventory data, which includes an interactive map and combines the digitized soil contours and parcel boundaries. In conclusion, one of the primary tasks for ensuring rational land use and soil protection should be the task of creating a database of soil cadastral data.